Regional Development and The Direction for Regional Development: Empirical Study in Bogor Regency (Sectoral and Spatial Approaches) - Rachmawatie, Dessy (Journal of Environmental Economics and Sustainability, 2023)
The regional approach aims to identify, analyze and evaluate the extent of regional development carried out by local governments, as well as to achieve regional development whether it is in accordance with the characteristics of the region. Bogor Regency plays an important role as a buffer area for DKI Jakarta. The high regional development and economic growth of DKI Jakarta has caused high population growth and high economic growth in Bogor Regency. However, the high economic growth does not guarantee economic equality in the region. The purpose of this study is to analyze and map regional development in Bogor Regency based on regional hierarchy and analyze the extent of equitable distribution of economic activities in Bogor Regency. The analsysis method used is using Regional Hierarchy Analysis and Overlay by Geographic Information System. The data used in this study used data on Gross Regional Domestic Income (GRDI). The results showed that the Regional Development Index in Bogor Regency in total continued to increase. However, if observed, the value of the coefficient of variation shows a significant increase. This shows an increase in inequality during that period of 32.057 percent.